PKM Business Plan bagi Kelompok Majelis Takim - Tenriwaru, Tenriwaru; Nurwanah, Andi; Syahnur, Haerdiansyah (Jurnal BALIRESO, 2024)
A business plan is a crucial document utilized by both external and internal audiences of a company. For instance, if the business plan is intended to attract investments, the company must articulate its plans to convince investors and creditors. While immensely beneficial for new businesses, every company should have a business plan. Ideally, this plan should be reviewed and updated periodically to assess whether goals have been achieved or have changed and evolved.This outreach program will teach the creation of a Business Plan to members of the Majelis Taklim as knowledge of business planning can support them in developing businesses, thus enhancing the welfare of members and families overall. Empowering mothers will aid in the development of villages, thereby realizing the equitable distribution of prosperity